Adverse Selection and Moral Hazard Effects in the Malaysian Credit Market: An Empirical Analysis (Malaysian Management Journal, 1997)
The purpose of this paper is to test empirically the impact of adverse selection and moral hazard on the Malaysian credit market. The paper develops a supply and demand function for credit in Malaysia by using monthly data over the period from January 1983 to November 1993 which has seen a recession and several years of sustained economic growth. Unconstrained 3SLS is used to estimate the model. The study shows that credit rationing is not practised in the Malaysian credit market, i.e., adverse selection is not present. However, commercial banks were willing to give more loans at higher interest rates which contributed to the problem of moral hazard. The reasons for the absence of credit rationing might be due to the enforcement of lending guidelines to the priority sectors during the period of the study and the concern of banks about their profitability which increases at higher interest rates. The policy implications of the findings are discussed.